Rethinking Islam in a Troubled World: Religious Themes in the Novels of Isa Kamari - Aveling, Harry (Asiatic: IIUM Journal of English Language and Literature, 2018)
Religion is a major topic in the novels of the prolific Singapore author Isa Kamari (1960-). In his earliest writing (One Earth, 2008), Islam is an unproblematic religion that offers clarity of doctrine, moral guidance in everyday life, psychological comfort and reassurance. It belongs, however, most naturally to small village situations and has begun to fail in larger urban contexts. Under the influence of globalisation and political resentment, a second movement has developed within Islam which places an emphasis on terrorism and violent action (Song of the Wind, 2009 and Intercession, 2010). A third and contrasting perspective focuses on the universal and inward spiritual nature of the Islamic revelation (Selendang Sukma, 2014 and The Tower, 2010). Isa’s latest work, Tweet (2016), is influenced by Attar’s mystical allegory, The Conference of the Birds (c. 1177), but argues for a spirituality that is committed to the transformation of worldly life in a positive and compassionate direction and not an escape from it.